Polycyclic aromatic chains on metals and insulating layers by repetitive [3+2] cycloadditions - Alexander Riss (Nature Portfolio, 2020)
A critical milestone for the advancement of nanoscale organic circuitry is the fabrication of well-defined conjugated polymers on non-metal substrates. Here, the authors demonstrate extended polycyclic aromatic chains from repetitive cycloadditions which form not only on metals, but also on boron nitride layers and in the solid state.